LSIM: a parallel programming environment for large-scale numerical computations - Natu, R.P.; Vargas, J.E. ([1991 Proceedings] The Twenty-Third Southeastern Symposium on System Theory, 1991)
This paper presents the work done in developing a Common LISP programming environment, to aid applications programmers solving large-scale numerical problems on hypercube architectures. The power of abstraction of Common LISP along with the speed of C programming language have been combined to develop this environment. The inherent parallelism and asynchronous operation of data-flow graphs are put to use in instruction execution.< >